Peranan Dinas Kependudukan dan Pencatatan Sipil Kota Bandar Lampung terhadap Implementasi Pasal 2 Peraturan Menteri dalam Negeri Nomor 02 Tahun 2016 tentang Kartu Identitas Anak Perspektif Siya - Mira Melinda; Yufi Wiyos Rini Masykuroh; Herlina Kurniati (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
The Identity Status of Children in Indonesia is contained in Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards article 1 paragraph (7) which reads: Child Identity Card, hereinafter abbreviated to KIA, is the child's official identity as proof of being a child who is less than 17 years old. and unmarried issued by the Regency/City Population and Civil Registration Service. The research method used is qualitative descriptive. The sampling technique used in this research is the Purposive Sampling method with 6 samples. Data collection techniques use observation, interviews and documentation. The data analysis technique uses qualitative analysis.The results of this research show that the implementation of Article 2 of the Minister of Home Affairs Regulation Number 2 of 2016 concerning Children's Identity Cards in the Bandar Lampung City Population and Civil Registration Service can be declared implemented as seen from the implementation of the Minister of Home Affairs Regulation Number 2 of 2016 concerning Children's Identity Cards in article 2 which explains the purpose of child identity cards so that the number of children who have Child Identity Cards from 2016 to 2024 is 309,758 children and in issuing child identity cards, the Population and Civil Registration Service has carried out its duties based on its authority and obligations and in Siya's view >Sah Tanfiz|iyah Syari'iyyah has been implemented in the community through a pick-up and drop-off program carried out by the Bandar Lampung City Population and Civil Registration Service which is in accordance with a leader (ulil amri) who must be responsible for the mandate that has been given and conveyed and carried out with the community according to tabligh characteristics and with Surah An-Nisa Verse 58.